Zsyłki biskupów katolickich w afrykańskim państwie Wandalów w relacji Wiktora z Wity - Milewski, Ireneusz (Vox Patrum, 2011)
The above article discusses one of the aspects of the Vandals’ religious policy in Africa, that is, deportations of Catholic bishops ordered by the Vandal kings. Of course, the Vandal kings were Arians and the fact itself defined their attitude towards Catholic clergy in North Africa, which they occupied. Describing the background of these deportations, their course and other repression which befell Catholic clergy (and the faithful) in Africa in the middle of the fifth century, we can only rely on the sources of Catholic authors, who had a negative attitude to the Vandals and their leaders. They portrayed them as crude and bloodthirsty tyrants, or even as psychopaths. Discussing the deportations of bishops in the reign of Genseric and Huneric, the background of the events was also presented. It was deduced that the underlying reason for the persecution of Catholics was the Vandals’ urge to consolidate their power in Africa. The bishops deprived of their seats were deported by the Vandal kings to Numidia (to the grounds controlled by the Moors) or to the islands of the Mediterranean Sea (Corsica, Sardegna) which belonged to the Vandals’ state. There they were forced to hard physical work (work on the land, cutting down trees used to build ships). Many of them, however, did not reach the assigned places of exile – they died on the way from physical exhaustion.